2016
DOI: 10.1083/jcb.201604081
|View full text |Cite
|
Sign up to set email alerts
|

53BP1 and USP28 mediate p53 activation and G1 arrest after centrosome loss or extended mitotic duration

Abstract: Meitinger et al. perform a genome-wide CRISPR/Cas9 screen for centrinone resistance and identify a 53BP1-USP28 module as critical for communicating mitotic challenges to the p53 circuit and TRIM37 as an enforcer of the singularity of centrosome assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
261
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(287 citation statements)
references
References 43 publications
24
261
2
Order By: Relevance
“…An alternative proposal is that mitosis could simply take more time in the haploids, but in the absence of mis-segregation. In this context, previous studies have shown that prolonged mitosis, even in the absence of segregation problems, leads to an USP28-, p53-, 53BP1-, and P21-dependent G1 arrest in the next interphase (32)(33)(34)(35). However, our findings of no increase in 53BP1 foci in haploid cells, apoptosis rather than G1 arrest in haploid cultures, and no increase in the percentage of haploid HAP1 cells on USP28 or P21 deletion (SI Appendix, Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…An alternative proposal is that mitosis could simply take more time in the haploids, but in the absence of mis-segregation. In this context, previous studies have shown that prolonged mitosis, even in the absence of segregation problems, leads to an USP28-, p53-, 53BP1-, and P21-dependent G1 arrest in the next interphase (32)(33)(34)(35). However, our findings of no increase in 53BP1 foci in haploid cells, apoptosis rather than G1 arrest in haploid cultures, and no increase in the percentage of haploid HAP1 cells on USP28 or P21 deletion (SI Appendix, Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…Importantly, p53 stabilized by PIDDosome activation after cytokinesis failure also lacked phosphorylation on Ser15. Whereas 53BP1 and USP28 are required for p53 induction upon extended mitotic timing but dispensable for p53-mediated cell cycle arrest upon cytokinesis failure (Fong et al 2016;Lambrus et al 2016;Meitinger et al 2016), we show that the PIDDosome is required for p53 stabilization upon cytokinesis failure but not upon prolonged mitotic timing or DNA damage. Of note, the latter two triggers do not rely on the generation of MDM2 cleavage fragments to activate p53 (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…p53 appears the most relevant effector responding to mitotic defects, inducing cell cycle arrest or cell death following aberrant mitoses (Vitale et al 2011). The triggers of mitotic defects can be very heterogeneous and include (1) DNA damage, occurring as either a consequence of sublethal caspase activation on extended mitosis (Orth et al 2012) or a result of chromosome segregation defects (Janssen et al 2011;Crasta et al 2012); (2) the extension of the mitotic duration itself above a critical threshold (Uetake and Sluder 2010;Fong et al 2016;Lambrus et al 2016;Meitinger et al 2016); (3) chromosome congression/segregation defects (Thompson and Compton 2010;Hinchcliffe et al 2016); and (4) cytokinesis failure or centrosome amplification (Holland et al 2012;Ganem et al 2014). While the first three cues appear clearly distinct from each other, either requiring a definite set of genetic factors for p53 activation or associating with specific markers, it remained elusive whether the presence of extra centrosomes suffices to trigger p53 activation or whether this occurs as a consequence of the resulting CIN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also reported that mitotic catastrophe-inducing events distinct from cytokinesis abortion, such as prolonged mitosis or DNA damage, initiated the p53 pathway via a mechanism not requiring CASP2 activity, which is in line with previous studies. 11,17,18 Finally, centrosome amplification was identified as the upstream signal triggering CASP2 activation upon cytokinesis abortion. 15 It remains to elucidate how and whether BCL9L and other factors responding to non-diploidy, including large tumor suppressor kinase 2 (LATS2) and the Hyppo pathway, 19 BCL2 proteins, 6 mitogen-activated protein kinase 14 (MAPK14, best known as p38), 9 Cyclin D1 (CCND1) 20 and ubiquitin specific peptidase 28 (USP28), 17,18 may contribute to this CASP2-dependent process.…”
mentioning
confidence: 99%